19‐3: Examination in Application of TOF‐SIMS with MS/MS to a Degradation Analysis of OLED. Issue 1 (29th May 2019) - Shirakura, Daichi; Suzuki, Aki; Okamura, Shinji; Akiyama, Takeshi; Shibamori, Takahiro; Miyamoto, Takashi; Sameshima, Junichiro
Abstract : TOF‐SIMS with MS/MS was applied to degradation analyses of OLEDs. Photoluminescence and GCIB‐TOF‐SIMS revealed a degraded layer and molecular weights of degradation products. MS/MS by TOF‐SIMS gave more detailed structural information of degradation products than conventional TOF‐SIMS, which demonstrated effectiveness of TOF‐SIMS with MS/MS for degradation analyses of OLEDs.